The role of activating schemata in pre-listening activities : - Lâm, Thùy Trang (Can Tho University, 2008)
The present research work attempts to contribute to understanding the practice of teaching listening skill. This study investigated belief of both teachers and students about the role of activating schemata in pre-listening activities in foreign language classes.